Media Digital Gimkit dalam Evaluasi Formatif Matematika Berbasis OBE di SMP - komarudin A (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2026)
This research aims to describe the use of Gimkit digital media in formative evaluation of Mathematics subjects based on the Outcome-Based Education (OBE) approach for class VII students at SMP Plus Darussalam Blokagung Banyuwangi. Formative evaluation is intended to determine students' competency achievements periodically during the learning process. The research method used was a qualitative descriptive approach, with research subjects being mathematics teachers and class VII students. Research instruments include observation, interviews, documentation of Gimkit quiz results, and formative evaluation sheets. The research results show that using Gimkit is able to increase student involvement in the evaluation process, provide real-time feedback, and make it easier for teachers to analyze learning outcomes. Gimkit's integration with OBE principles shows that 83% of students can achieve learning indicators through fun and interactive formative evaluations. Keywords: Gimkit, Formative Evaluation